Réponses

2014-01-29T17:36:00+01:00
E= 7(2x-5) - (2x-5)²
E= (2x-5) (7 - 2x + 5)
E= (2x-5) (-2x + 12)

E= 7(2x-5) - (2x-5)²
E= 7( 2 x √5 - 5 ) - (2 x √5 - 5)²
E= 7(2√5 - 5) - (4√25 + 25)
E= 14√5 - 35 - (20√5 + 25)
E= 14√5 - 35 - 20√5 - 25
E= -6√5 - 60

E= 7(2x-5) - (2x-5)²
E= 7( 2 x 5/2 - 5) - (2 x 5/2 - 5)²
E= 7(10/2 - 5) - (100/4 + 25)
E= 7(0) - (25+25)
E= 0 - 50 
E= -50 

E= (2x-5) (-2x+12)
E= 2x-5 = 0 OU -2x + 12 = 0
E= 2x = 5 OU -2x = -12
E= x = 5/2 OU -x = -6
E= x = 5/2 OU x = 6 

Voilàa 
pourquoi dans l'équation au premier E tu a marquer 12 ?
où sa ?